The Experimental Design of Stone Columns’ Modelling using Small-Scale Unit Cells: A Review - A. Almaliki, Bahaa; R. Selamat, Mohamad (International Journal of Engineering and Technology, 2018)
This paper presents a review of the experimental design of the small-scale single stone column that adopts the unit cell concept. Materials and methods used in experiments along with their effects and implication have been appraised. The reviewed cases showed that clayey soils were often used to construct the host ground. Steel cylindrical tanks were used with diameters ranging from 15 to 60 cm and heights ranging from 20 to 120 cm. For such scale, the used stone size is 2 to 10 mm. Plates load test can be carried out on the entire tank or on the stone column. The load has been imposed at a constant settlement rate of 1 to 1.25 mm/min in order to simulate the stage immediately after construction. The review shows that remoulding and replacement have been often practised for the construction of the host ground and the stone column, respectively.Â Â